The Development of AWQAF Institutions in Nigeria for Sustainable Community Development and Poverty Eradication (Global Journal of Human-Social Science, 2013)
In the whole of black Africa, South Africa is the only country known to be practicing Awqaf institutions. However, seven years ago Muslim community at Obafemi Awolowo University in Nigeria commenced the practice. Nigeria is a huge Muslim population country. More than half of the entire population of the country is Muslim. However, 90 percent of this Muslim population is located in the Northern and Western parts of the country. This explains why Awqaf institutions are mostly located in these two out of three regions of the country. Just as there are national Awqaf institutions so are there state and local variants of them. In fact, institutional Awqaf institutions e.g. Universities and other tertiary institutions, also exist. Obafemi Awolowo University, Ile-Ife, as an educational institution with active Awqaf institutions has the following granite Islamic bodies or organizations that operate Awqaf: Obafemi Awolowo University Muslim Community (OAUMC); Vanguard of Islam (V I); Association of Muslim Professional (AMP); University of Ife Muslim Graduate Association (UNIFEMGA); Federation of Muslim Women's Association in Nigeria (FOMWAN); Obafemi Awolowo University Trust Cooperatives (OAUTC), Kudiratulai (KL), Muslim Family Forum (MFF), and Muslim Student Society of Nigeria OAU branch (MSS). It is part of the mission of these bodies to embark on community development projects as well as eradicating poverty within the University community and outside it as well 1 .